2022
DOI: 10.1007/s11356-022-19239-2
|View full text |Cite|
|
Sign up to set email alerts
|

Pathways to decarbonization in India: the role of environmentally friendly tourism development

Abstract: The paradigm of sustainable tourism policy implications aims to prioritize the decoupling association between tourism development and environmental deterioration. The study revisits the dynamic associations among carbon dioxide emissions, economic growth, international tourism, education, renewable energy consumption, and gross capital formation for the case of India through the lens of the environmental Kuznets curve hypothesis framework. The long-run dynamics among the variables confirm the inverted U-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 112 publications
2
7
0
Order By: Relevance
“…This validates the EKC notion in light of Narayan and Narayan [53]. Prior research, such as Rej et al [64] for India, Awan et al [65] for ten developing countries, and Agboola et al [66] for Turkey, has shown similar results, while Rej et al [67] and Islam et al [51] have shown contrasting outcomes. The technique utilized, the dependent variable analyzed, and the time span of the study might all account for these discrepancies in results.…”
Section: Resultssupporting
confidence: 81%
“…This validates the EKC notion in light of Narayan and Narayan [53]. Prior research, such as Rej et al [64] for India, Awan et al [65] for ten developing countries, and Agboola et al [66] for Turkey, has shown similar results, while Rej et al [67] and Islam et al [51] have shown contrasting outcomes. The technique utilized, the dependent variable analyzed, and the time span of the study might all account for these discrepancies in results.…”
Section: Resultssupporting
confidence: 81%
“…Paramati et al (2017), Raza et al (2017), and Bella (2018) concluded that the adaptation of sustainable tourism policies and efficient management could change the level of CO 2 emissions from the tourism industry. Rej et al (2022) found evidence for the existence of an inverted U-shaped Environmental Kuznets Curve (EKC) for tourism development in India; the research showed that a higher number of tourist arrivals, capital, and renewable energy use would curb emissions in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, in the long run, economic growth will play a positive and significant role in the use of renewable energy [20] Katircioglu et al [21] examined the impact of tourism growth on the emission of pollutants in the northern part of Cyprus and showed that tourism has a significant long-term impact on carbon emission levels and that tourism growth would lead to environmental deterioration. Rej et al [22] argued that paradigms of sustainable tourism policy impact are designed to prioritize the decoupling link between tourism development and environmental degradation and confirmed that higher international tourist numbers, use of renewable energy, and total capital formation can curb emissions in the long run. Surprisingly, for developing economies such as Sub-Saharan Africa (SSA), machinery imports can also significantly reduce carbon emissions, but not as much as renewable energy [23].…”
Section: Literature Reviewmentioning
confidence: 99%